A meta-core outcome set for stillbirth prevention and bereavement care following stillbirth in LMIC - Jamie J Kirkham; Declan Devane; Carol Bedwell; Tina Lavender; Tracey A Mills; Sabina Wakasiaka; Rose Laisser; Bellington Vwalika; Nasim Chaudhry; Angela Chimwaza; Elizabeth Ombeva Ayebare; Sudhindrashayana Fattepur; et al. (BMJ Global Health)
Study objective Stillbirth is burdensome in low-income and middle-income countries (LMICs), especially in sub-Saharan Africa and South Asia. Currently, there are two core outcome sets (COS) for stillbirth (prevention and bereavement care), but these were developed with limited reflection of the needs of parents in an LMIC setting. To address this gap, the objective of this study was to establish consensus on the most important outcomes for stillbirth prevention and bereavement care following stillbirth in sub-Saharan Africa and South Asia.Methods Previous stillbirth outcomes were reviewed for inclusion into the COS by senior research leaders and community engagement and involvement members from six sub-Saharan African and two South Asian countries. An online real-time Delphi survey was then conducted with healthcare professionals, parents who have experienced a stillbirth and researchers in the field to score the agreed list. The results of the Delphi were summarised and then discussed at a virtual consensus meeting where the final COS were agreed.Results 287 participants contributed towards the Delphi (143 midwives, 32 obstetricians, 50 mothers, 12 fathers and 50 researchers), with at least 2 parents attending the full consensus meetings. Consensus was reached on 13 core outcomes for stillbirth prevention covering 5 domains: obstetric, fetal, perinatal and neonatal outcomes and maternal complications. For bereavement care following a stillbirth, five core outcomes reached a consensus, which included outcomes related to labour and birth, a postpartum complication, care experience, mental health and emotional and social well-being.Discussion These COS will improve the consistency of outcomes for future research in an LMIC setting. Additionally, they will complement existing COS for stillbirth prevention and bereavement care developed in high-income settings. The output from this work will move us towards a global set of outcomes that can be used in stillbirth research worldwide.